Answer:
(x - 3)(2x + 7)
Step-by-step explanation:
Assuming you require the expression factorised.
Given
2x² + x - 21
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 21 = - 42 and sum = + 1
The factors are - 6 and + 7
Use these factors to split the x- term
2x² - 6x + 7x - 21 ( factor the first/second and third/fourth terms )
= 2x( x - 3) + 7(x - 3) ← factor out (x - 3) from each term
= (x - 3)(2x + 7) ← in factored form